Application of betel leaves (Piper betle L.) extract for preservation of homemade chili bo - Voon, Wendy Wen Yi; Ghali, Nur Atikah; Rukayadi, Yaya; Meor Hussin, Anis Shobirin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
This study is conducted to investigate the effect of different concentrations of betel leaves extract on color, pH and microbiological in homemade chili bo. The homemade chili bo with different concentrations (0 mg/ml, 0.75 mg/ml, 1.25 mg/ml and 1.75 mg/ml) of betel leaves extract were prepared for analysis. The results showed that the color of chili bo became darker as the concentration of betel leaves extract increased. The extract showed significant in the pH of chili bo after 7 days in which the highest concentration of extract showed the highest value of pH 4.31. The aerobic microbial count was decreased as the concentration of betel leaves extract increased in chili bo. After 7 days of storage, the highest concentration of betel leaves extract showed the highest percentage of reduction (6%), while the control sample showed 2.41% of aerobic reduction. The study also found that the extract contain lesser yeast and mold count (5.22 log CFU/ml) in homemade chili bo compared to the control sample (5.31 log CFU/ ml) after 7 days. Betel leaves extract can be considered as natural food preservatives in chili bo to reduce the growth of spoilage microorganism and thus enhance the shelf life of chili bo.